PENERAPAN MEDIA PEMBELAJARAN POP-UP BOOK ANAK USIA DINI PADA KELOMPOK B UNTUK MENINGKATKAN KEMAMPUAN KEAKSARAAN AWAL DI TK NUSA INDAH - Rapi Halipani Matin; Euis Ety Rohaety; Lenny Nuraeni (IKIP Siliwangi, 2019)
One important aspect developed in early childhood is the ability of early literacy. For this reason, we need a learning media that can improve children's early literacy skills, one of which is pop-up book learning media. The purpose of this study was to determine the effect of using pop-up book learning media on children's early literacy abilities. This study used the Quasi Experiment method with the Nonequevalent Control Group Design research design. The pre-test results showed that there was no significant difference in the experimental group and the control group with a p-value> 0.05 which was 0.065> 0.05 which was tested by the Mann Whitney test results. While the post-test results showed that the initial literacy ability after the application of the pop-up book learning media had a significant difference with the p-value <0.05 which was 0.236. Thus the pop-up book learning media significantly influences early childhood literacy abilities. Based on this study, the study recommends early childhood educators so that the pop-up book learning media can be used as a medium of learning to improve children's early literacy skills.